Spatial Variation of Soil Chemical Properties in Industrial Wastewater Contaminated Paddy Soil (Journal of Environmental Science and Natural Resources, 2017)
Soil quality is essential for sustainable crop production. Excessive or deficient in necessary chemical elements in soil is a concern for soil quality. The study was undertaken to evaluate the impact of chemical industrial wastewater on chemical properties of soil and observe spatial distribution of nutrients in paddy soil adjacent to a chemical industry. A command area comprising a paddy field exposed to a chemical industrial wastewater was selected to study and 10 composite soil samples including a control (not exposed to wastewater) was collected and analyzed. Compared to background values soil pH, OC, N, P, Ca, and S were found higher in contaminated soils through the industrial wastewater. The order of the increment of the nutrients in the contaminated soil was as N>P>S>OC>Ca>Na. Sulphur and Nitrogen pose as potent elements for toxicity or pollution of the soil exposed to untreated wastewater. Differential spatial variations were observed for various nutrients in the area. Highest spatial variation was observed for S, N and B followed by P, K, Ca, Mg and Na might be due to anthropogenic activities through industrial untreated wastewater. These issues need to be taken into consideration while recommending fertilizers for crops grown in this type of command area.J. Environ. Sci. & Natural Resources, 9(2): 85-90 2016